Mapping of Membrane Lipid Order in Root Apex Zones of Arabidopsis thaliana - Zhao, Xiaoyu; Zhang, Xiran; Qu, Yanli; Li, Ruili; Baluška, František; Wan, Yinglang (Frontiers in Plant Science, 2015)
In this study, we used the fluorescence probe, Di-4-ANEPPDHQ, to map the distribution of membrane lipid order in the apical region of Arabidopsis roots. The generalized polarization (GP) value of Di-4-ANEPPDHQ-stained roots indicated the highest lipid order in the root transition zone. The cortical cells have higher lipid order than the epidermal cells in same regions, while the developing root hairs show very prominent cell polarity with high lipid order in apical region. Moreover, the endosomes had lower lipid order than that of the plasma membrane. Brefeldin A treatment decreased the lipid order in both the plasma and endosomal membranes of epidermal cells in the root transition zone. The lipid order of brefeldin A-induced compartments became higher than that of the plasma membrane after brefeldin A treatment in epidermal cells. Meanwhile, the polarly growing tips of root hairs did not show the same behavior. The lipid order of the plasma membrane remained unchanged, with higher values than that of the endosomes. This suggests that the lipid ordering in the plasma membrane was affected by recycling of endosomal vesicles in epidermal cells of the root apex transition zone but not in the root hairs of Arabidopsis.